Revising the mechanism of p75NTR activation: intrinsically monomeric state of death domains invokes the "helper" hypothesis - Sergey A. Goncharuk; Lilya E. Artemieva; Kirill D. Nadezhdin; Alexander S. Arseniev; Konstantin S. Mineev (Scientific Reports, 2020)
Abstract The neurotrophin receptor p75NTR plays crucial roles in neuron development and regulates important neuronal processes like degeneration, apoptosis and cell survival. At the same time the detailed mechanism of signal transduction is unclear. One of the main hypotheses known as the snail-tong mechanism assumes that in the inactive state, the death domains interact with each other and in response to ligand binding there is a conformational change leading to their exposure. Here, we show that neither rat nor human p75NTR death domains homodimerize in solution. Moreover, there is no interaction between the death domains in a more native context: the dimerization of transmembrane domains in liposomes and the presence of activating mutation in extracellular juxtamembrane region do not lead to intracellular domain interaction. These findings suggest that the activation mechanism of p75NTR should be revised. Thus, we propose a novel model of p75NTR functioning based on interaction with “helper” protein.